Pengaruh Budaya Organisasi dan Pelatihan terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Kantor Camat Lubuk Sikarah Kota Solok - Annisa Salsabilla; Dori Mittra Candana; Selvi Zola Fenia (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to determine the effect of Organizational Culture and Training on Employee Performance with Work Motivation as an Intervening Variable at the Lubuk Sikarah District Office in Solok City, under the supervision of Dr. Dori Mittra Candana, SE, M.M., and Mrs. Selvi Zola Fenia, S.Psi, M.M. This is a quantitative study. Data collection was carried out through questionnaires, with a sample of 60 respondents at the Lubuk Sikarah District Office in Solok City. The analysis methods used are path analysis, partial least squares (PLS), outer model, inner model, and hypothesis testing. Data processing in this study was done using the SmartPLS 3.0 software.The research results can be concluded as follows: Organizational Culture has a positive and significant effect on Work Motivation; Training has a positive and significant effect on Work Motivation; Organizational Culture has a positive and significant effect on Employee Performance; Training has a positive and significant effect on Employee Performance; Work Motivation has a positive but insignificant effect on Employee Performance; and Organizational Culture can mediate the relationship between Training and Employee Performance with Work Motivation as the intervening variable at the Lubuk Sikarah District Office in Solok City.